2017
DOI: 10.1007/s10897-017-0096-5
|View full text |Cite
|
Sign up to set email alerts
|

Insights into BRCA1/2 Genetic Counseling from Ethnically Diverse Latina Breast Cancer Survivors

Abstract: Despite the disproportionate underuse of genetic counseling and testing for BRCA1/2 (BRCA)-associated hereditary breast and ovarian cancer (HBOC) risk among Latinas, little is known about the associated barriers and facilitators. We conducted in-depth qualitative interviews with 20 at-risk Latina women from diverse backgrounds. Eligible women were diagnosed with breast cancer <50 years, with or without a family history of breast and/or ovarian cancer (>1 first-degree relative diagnosed <50 years). All intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 56 publications
4
33
0
Order By: Relevance
“…Reinforcing findings reported from studies with Latina patients, motivators to participate in GCRA included informing family risk, informing treatment/prevention decisions, and following doctors’ recommendations. Also consistent with prior work was providers’ identification of barriers related to included cost/insurance, suboptimal referrals, awareness, language, education, and stigma [ 20 , 26 , 29 , 43 , 44 , 45 ]. Below we identify where the present study findings expand prior work.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Reinforcing findings reported from studies with Latina patients, motivators to participate in GCRA included informing family risk, informing treatment/prevention decisions, and following doctors’ recommendations. Also consistent with prior work was providers’ identification of barriers related to included cost/insurance, suboptimal referrals, awareness, language, education, and stigma [ 20 , 26 , 29 , 43 , 44 , 45 ]. Below we identify where the present study findings expand prior work.…”
Section: Discussionsupporting
confidence: 59%
“…Evidence from community samples suggest that Latinas may be less likely to receive counseling. In a small study that included 20 at-risk Latina breast cancer survivors recruited from community settings, only 35% had testing and none received counseling [ 44 ]. Future research can examine outcomes among patients with and without genetic counseling and also explore if alternative genetic counseling delivery models, such as streamlined approaches to pre-test genetic education [ 48 ] may yield benefits in terms of reach and efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…These patients are less likely to understand or adhere to care plans and are less satisfied with the care they receive (Gregg & Saha, ; Jacobs, Chen, Karliner, Agger‐Gupta, & Mutha, ). Similar findings have been shown for patients receiving genetic counseling for a variety of indications when counseling is not provided in their preferred language (Cruz‐Correa et al, ; Rajpal, Muñoz, Peshkin, & Graves, ).…”
Section: Process For Adding a New Language To Lexigene®supporting
confidence: 78%
“…Baseline levels of understanding of the process of genetic counseling are low in the general population despite increased availability of genetic counseling services (Allen, Roberts, & Guan, 2019;Maio, Carrion, Yaremco, & Austin, 2013). In some racial and ethnic communities, the vast majority of people have little or no familiarity with the field of genetic counseling (Awwad, Veach, Bartels, & LeRoy, 2008;Rajpal, Muñoz, Peshkin, & Graves, 2017;Sheppard et al, 2014;Sussner et al, 2014). Racial and ethnic disparities in access to and participation in genetics research, testing, and counseling have been identified (Armstrong, Micco, Carney, Stopfer, & Putt, 2005;Butrick et al, 2015;Levy et al, 2011;Peters, Rose, & Armstrong, 2004;Suther & Kiros, 2009).…”
mentioning
confidence: 99%